2015
DOI: 10.1016/j.marpolbul.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Deepwater Horizon oil and associated dispersant on early development of the Eastern oyster Crassostrea virginica

Abstract: The explosion of the Deepwater Horizon (DWH) oil platform resulted in large amounts of crude oil and dispersant Corexit 9500A® released into the Gulf of Mexico and coincided with the spawning season of the oyster, Crassostrea virginica. The effects of exposing gametes and embryos of C. virginica to dispersant alone (Corexit), mechanically (HEWAF) and chemically dispersed (CEWAF) DWH oil were evaluated. Fertilization success and the morphological development, growth, and survival of larvae were assessed. Gamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 64 publications
10
28
0
Order By: Relevance
“…Unfortunately, they only reported adverse effects of CEWAF on larval survival and larval growth was not assessed. In a previous study, fertilization success and particularly early larval growth of oysters were shown to be negatively affected by exposure to DWH oil/dispersant and to be sensitive toxicological endpoints (Vignier et al, 2015). At equivalent nominal concentrations, dispersed oil (CEWAF) and dispersant alone also showed similar toxicity responses of early life stages of oysters, indicating that most of the toxicity of CEWAF was associated with the Corexit itself (Vignier et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Unfortunately, they only reported adverse effects of CEWAF on larval survival and larval growth was not assessed. In a previous study, fertilization success and particularly early larval growth of oysters were shown to be negatively affected by exposure to DWH oil/dispersant and to be sensitive toxicological endpoints (Vignier et al, 2015). At equivalent nominal concentrations, dispersed oil (CEWAF) and dispersant alone also showed similar toxicity responses of early life stages of oysters, indicating that most of the toxicity of CEWAF was associated with the Corexit itself (Vignier et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…, Vignier et al. ), and low salinities reduce survival of L. irrorata larvae (Bingham ). No studies, however, directly measured the abundance of L. irrorata larvae or immediately post‐metamorphic juveniles in Louisiana during these years, so we lack any direct evidence of these putative mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the loss and possible reproductive failure of adults at these sites would have caused some reduction in the larval pool, this mechanism cannot explain the recovery of Littoraria population structure after 2011 because densities of Littoraria at oiled sites remained suppressed for more than a year after the spill (Zengel et al 2015). Deepwater Horizon oil was toxic to some marine invertebrate and vertebrate larvae (Goodbody-Gringley et al 2013, Incardona et al 2014, Vignier et al 2015, and low salinities reduce survival of L. irrorata larvae (Bingham 1972a). No studies, however, directly measured the abundance of L. irrorata larvae or immediately post-metamorphic juveniles in Louisiana during these years, so we lack any direct evidence of these putative mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Following spawning and fertilization, developing free-swimming C. virginica larvae spend 2 -3 weeks in the water column, usually floating near the surface, until they settle on a suitable substrate (Bahr and Lanier, 1981). Recent studies have demonstrated the toxic effects of DWH crude oil on the early life stages of C. virginica , notably, damage to sperm and oocyte functions causing a reduction in fertilization success (Volety et al, 2016;Vignier et al, 2017), an increase in embryo and larval defects, retardation in larval growth and a decline in settlement success, and ultimately mortalities (Laramore et al, 2014;Vignier et al, 2015Vignier et al, , 2016Langdon et al, 2016;Stefansson et al, 2016;Finch et al, 2016Finch et al, , 2018Boulais et al, 2018).…”
Section: Introductionmentioning
confidence: 99%